Pedestrianization around the San José market determining the walkability index - Sandoval Alfaro, César (2024)
The present study responds to the problem that afflicts the citizens of the Jesús María district, mainly those who live in the buildings located around the San José market, due to the excessive use of street parking. In this sense, the objective of this research aims to improve the quality of life of residents, visitors and merchants in the area, promoting the pedestrianization of the streets located around the aforementioned supply center, by determining the walkability indices and surveys that will support the proposals made. The project contemplates the elimination of parking lots in the streets adjacent to the market, and the creation of exclusive areas for pedestrian traffic, a measure that will allow passers-by to walk with greater safety and comfort, in addition to promoting economic activity around the market. by creating a more attractive and accessible environment, thus obtaining inclusive, healthy, resilient and sustainable developments.